Pengaruh Perputaran Piutang dan Perputaran Kas terhadap Likuiditas - Eka Astuti (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2013)
The purpose of this study to determine whether the turnover of receivables and cash turnover effect partially or simultaneously on the level of liquidity. The research method use quantitative methods, or statistical analysis. The populations in this study are all consumer goods companies listed on the Indonesia Stock Exchange for the period 2011. 32 samples were taken using purposive sampling technique. Testing the hypothesis using multiple linear regressions with the t test and F test The results showed that the partial turnover has no effect on liquidity. The results showed that the velocity of cash was also no effect on liquidity. Simultaneously, cash turnover and turnover affect liquidity.